Transcriptional Regulation of CYP2D6 by Nrf2 and Its Implications in Breast Cancer Therapy: Bioinformatics and Experimental Evidence - Ferbian Milas Siswanto; Maria Dara Novi Handayani; Lonah Lonah; Rita Dewi; Zita Arieselia; Linawati Hananta; Putu Suwarastra Andarisuta (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Tamoxifen (TAM) resistance in patient with breast cancer is the leading cause of mortality among women globally. Cytochrome P450 2D6 (CYP2D6) is involved in the metabolism of TAM, and recently NF-E2-related factor 2 (Nrf2) has recently been found as its regulator. However, the impact of Nrf2-mediated CYP2D6 regulation in the context of breast cancer and TAM resistance are currently unknown. Therefore, this study was conducted to examine the role of CYP2D6 and Nrf2 in breast cancer prognosis. MEDTHODS: The roles of CYP2D6 and Nrf2 were investigated in the T47D breast cancer cell line and T47D-derived TAM-resistant cells by examining the gene expression, cell viability, and transcriptional regulation by quantitative reverse transcription polymerase chain reaction (qRT-PCR), MTT, and reporter gene assay, respectively. Additionally, comprehensive in silico analysis of the transcriptomic and clinical data from The Cancer Genome Atlas database were performed to uncover the prognostic role of CYP2D6 and its regulator in breast cancer patients. RESULTS: CYP2D6 mRNA was low and Nrf2 protein was high in TAM-resistant T47D cells compared to parental cells. Nrf2 knockdown upregulated CYP2D6 mRNA levels and enhanced the cytotoxicity of TAM. Similarly, in silico analysis revealed that low CYP2D6 mRNA and high Nrf2 protein were related to a lower probability of survival. The rs1238662089 within the identified Nrf2-binding site was found to greatly affect CYP2D6 expression levels, indicating its role as predictor for better prognosis. CONCLUSION: This study revealed for the first time that Nrf2 regulates CYP2D6expression in breast cancer and is involved in TAM sensitivity; thus, plays a role in breast cancer patient prognosis.KEYWORDS: breast cancer, CYP2D6, Nrf2, pharmacoepigenetics, SNPs